Determinants of Workers’ Remittances in Nepal: An Empirical Study (Quest Journal of Management and Social Sciences, 2021)
Background: Remittance has a crucial role in external sector stability, poverty eradication, and social as well as the human development of developing countries like Nepal. The determinants of remittance are widely discussed in the existing works of literature from altruism and portfolio approaches. Since the share of remittance in the current account, current transfer income, and forex reserve is significantly high, the study of major determinants of increasing remittance inflow is necessary. In this regard, this paper examines the relationship between remittance inflow, exchange rate, and workers outflow in Nepal.Objective: The main objective of this study was to examine the effect of the exchange rate and workers outflow on the remittance inflow of Nepal.Methods: This study employs the ARDL approach to co-integration to examine the relationship between remittance inflow as an endogenous variable and exchange rate and workers outflow as exogenous variables.Results: The coefficients of the exchange rate and workers outflow are significant and positive in long run as well as in the short-run whereas coefficients of the first lag value of workers outflow and remittance inflow itself are significant but negative.Conclusion: The significant and positive coefficient of exchange rate indicates that depreciation of Nepalese currency with US dollar (or rise in the exchange rate) rises the remittance inflow. Further, the remittance inflow also increases with an increase in workers outflow. The effect of the exchange rate on remittance is greater than that of workers outflow in both the long-run and short-run.